Challenges Facing Groundwater Management in Sudan (University of Khartoum Engineering Journal, 2022)
Sudan has great potential of renewable and non-renewable groundwater resources which are importantsources of water supply for domestic, industrial and agricultural uses. It is a key element for human settlement andsustained socioeconomic activities. Demand for groundwater in many areas of the Sudan has recently increasedconsiderably in order to meet the needs for the implementation of agricultural and economic development plansbut regrettably, these development are taking place in a rather unplanned manner leading to many problems suchas overexploitation, reduction of reliable yield, and deterioration of quality .This emphasizes the need for soundpolices and optimum plans for groundwater resources management in order to ensure its long term sustainability.However, Groundwater management in Sudan is faced with many challenges. The most obvious of thesechallenges is the absence of quantitative and qualitative monitoring and scarcity of information on aquifersgeometry and their hydro geological characteristics. Another major difficulty is related to the understanding offlow dynamics and recharge sources and mechanisms for the different aquifers. This makes the estimation ofrecharge volumes an extremely difficult task. Correct estimation of groundwater recharge and aquifer storage aretwo of the most important requirements for long term management of any groundwater system. Fractured aquifersin Sudan cover very large areas and provide an important source of water particularly in rural areas. A majorproblem encountered in the management of fractured aquifers is the limited understanding of their hydrogeologyand flow dynamics. The fractures characteristics could be extremely complex making it very difficult to locateareas of productive boreholes with sustainable groundwater yield. Vulnerability and risk of contamination of theseaquifers are also very high. Other key challenges facing groundwater management in Sudan are the managementof shared non-renewable aquifer resources, lack of comprehensive guiding plans and policies, poor governanceand legislative framework, inadequate capacity, and lack of coordination among groundwater sub sectors.Thepurpose of this paper is to discuss these challenges in some details and suggest directions for overcoming them.The paper also includes a case study on the use of advanced methodologies for groundwater management andprotection in Sudan.